Ateliers de potiers médiévaux en Bretagne - Fichet de Clairfontaine, François (Documents d'archéologie française, 1996)
A research project carried out between 1984 et 1989 permitted a multidisciplinary approach to the problem of the history of medieval pottery production centres in Brittany to be studied by a dialogue between history, archeology and archaeometry. Diachronic studies of the written sources (XIVth-XXth centuries), fieldwork and studies of the geological and archeological environment were systematically carried out, the excavation of two Carolingian production sites (Meudon near Vannes and Plangueuoual, Côtes-d'Armor) or from XIth-XIIth centuries (Fontenay in Chartres-de-Bretagne); these being axed on sise totality of the workshop structures and not only on the kilns, the analysis of the products (morphological analysis, petrographical characterisation and archaeomagnetic dating). This research, feed by methodological techniques, comprises ten contributions each reflecting the diverse approaches and the renewal of interest in the history of pottery workshops and centres rti Brittany.